Child feces disposal practices in rural Orissa: a cross sectional study. - Fiona Majorin; Matthew C Freeman; Sharmani Barnard; Parimita Routray; Sophie Boisson; Thomas Clasen (PLoS ONE)
Background An estimated 2.5 billion people worldwide lack access to improved sanitation facilities. While large-scale programs in some countries have increased latrine coverage, they sometimes fail to ensure optimal latrine use, including the safe disposal of child feces, a significant source of exposure to fecal pathogens. We undertook a cross-sectional study to explore fecal disposal practices among children in rural Orissa, India in villages where the Government of India's Total Sanitation Campaign had been implemented at least three years prior to the study. Methods and findings We conducted surveys with heads of 136 households with 145 children under 5 years of age in 20 villages. We describe defecation and feces disposal practices and explore associations between safe disposal and risk factors. Respondents reported that children commonly defecated on the ground, either inside the household (57.5%) for pre-ambulatory children or around the compound (55.2%) for ambulatory children. Twenty percent of pre-ambulatory children used potties and nappies; the same percentage of ambulatory children defecated in a latrine. While 78.6% of study children came from 106 households with a latrine, less than a quarter (22.8%) reported using them for disposal of child feces. Most child feces were deposited with other household waste, both for pre-ambulatory (67.5%) and ambulatory (58.1%) children. After restricting the analysis to households owning a latrine, the use of a nappy or potty was associated with safe disposal of feces (OR 6.72, 95%CI 1.02-44.38) though due to small sample size the regression could not adjust for confounders. Conclusions In the area surveyed, the Total Sanitation Campaign has not led to high levels of safe disposal of child feces. Further research is needed to identify the actual scope of this potential gap in programming, the health risk presented and interventions to minimize any adverse effect.